Problems and Prospects of SMEs Loan Management: A Study on Mercantile Bank Limited, Khulna Branch - Akterujjaman, SM (Journal of Business and Technology (Dhaka), 2012)
SMEs all over the world have been playing a crucial role in promoting economic development as well as industrial production. SME financing has been identified as a major obstacle to SME growth. Unfortunately, the issue seems to be as unresolved as it always has been. Though the majority of the issues are with the SME themselves, the banks also have major issues in designing financial products for the SMEs. This study tries to find out the underlying problems from the bank’s perspective. The major findings are related to the high interest and loan duration rates, reasons for SMEs relatively informal way of doing business in contrast to bank’s formal procedures and prerequisites, bank’s relative inexperience in this field. They are also related to the bank’s lack of perspective, the viability and benefits of cluster unity, approach to informal loan takers and non-usage of modern technology and accounting procedures. The recommendations were provided based on the analysis and findings. Key words: Small and Medium Enterprises (SMEs); Financing; Loan; Technology; Cluster. DOI: http://dx.doi.org/10.3329/jbt.v5i2.9934 Journal of Business and Technology (Dhaka) Vol. 5(2), July-December, 2010 38-52